Comparison of Sizes, Morphologies and Optical Properties of NiO Nanostructures Synthesized Using Acetate and Nitrate Anions from Nickel Salts via Hydrothermal Method - Pranwadee Kaewmuang (Science Faculty of Chiang Mai University, 2019)
Porous NiO nanocrystals were synthesized using a hydrothermal method in mediums of different anions from nickel salts, acetate (CH3COO-) and nitrate (NO3-),followed by calcination at 500 °C. Firstly, b-Ni(OH)2 powders with a hexagonal structure were formed. Using acetate and nitrate anions, the obtained b-Ni(OH)2 powders were composed of thin nanosheets (0.8-2.1 mm in length), and a splinter-like structure self-assembled with longer nanosheets (9.8-24.2 mm), respectively. The difference in the interaction ability between the anions and the b-Ni(OH)2 surfaces, affecting the growth behavior of the crystals, was examined using the density functional theory (DFT) method. After calcination, the b-Ni(OH)2 turned into porous NiO with a cubic structure but their morphologies were unchanged. The porous NiO with longer nanosheets possessing higher crystallinity and larger surface area provided better UV-Vis absorption ability.